Aconitine synthesis studies. A modeling construction of the functionalized BCDE tetracyclic ring system. Issue 3 (19th December 2022) - Guo, Tianyuan; Peng, Fuli; Song, Xueqin; Lei, Jiang; Yu, Fangzhou; Chu, Hongping; Yang, Keyang; Xu, Liang
Abstract : A highly functionalized BCDE model ring system of aconitine has been synthesized for the first time via a strategy involving oxidative dearomatization/IMDA, Wagner–Meerwein rearrangement, Michael addition and reductive cyclization. Abstract : The first model synthesis of the fully functionalized BCDE tetracyclic analogue 2 of aconitine has been accomplished. A tricyclic intermediate was prepared through highly stereospecific reduction of the ketone intermediates 14 and 16 as well as the following facile Wagner–Meerwein rearrangement. A stereoselective Michael addition and reductive cyclization involving a sequential nitrile hydration and silane promoted reduction were exploited to construct the nitrogen containing six-membered E ring bearing vicinal tertiary and quaternary centers.